2010
DOI: 10.1099/jmm.0.018978-0
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a shift towards penicillin resistance in the Streptococcus uberis population

Abstract: Demonstration of a shift towards penicillin resistance in the Streptococcus uberis population Penicillin resistance has been particularly well studied in Streptococcus pneumoniae (Denapaite et al., 2007; Hoban et al., 2005). In this organism, resistance frequently occurs through modifications of the penicillin-binding proteins (PBPs) and/or the generation of mosaic PBPs, leading to a decreased affinity for the drug (Nagai et al., 2002). Among clinically relevant streptococci, S. pneumoniae primarily infects hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…Pirlimycin resistance among streptococci has been reported previously (Rossitto et al, 2002;Pol and Ruegg, 2007a;Schmitt-Van de Leemput and Zadoks, 2007;GERMAP, 2008;Haenni et al, 2010). In the present study, high levels of pirlimycin resistance (MIC ≥16 mg/L) were found (Table 1), whereby Strep.…”
Section: Short Communicationsupporting
confidence: 74%
See 2 more Smart Citations
“…Pirlimycin resistance among streptococci has been reported previously (Rossitto et al, 2002;Pol and Ruegg, 2007a;Schmitt-Van de Leemput and Zadoks, 2007;GERMAP, 2008;Haenni et al, 2010). In the present study, high levels of pirlimycin resistance (MIC ≥16 mg/L) were found (Table 1), whereby Strep.…”
Section: Short Communicationsupporting
confidence: 74%
“…Decreased susceptibility to penicillin has, however, been reported previously (Erskine et al, 2002;Guérin-Faublée et al, 2002;Rossitto et al, 2002). Haenni et al (2010) reported that a subpopulation of Strep. uberis field isolates shifted toward resistance against penicillin, despite the fact that all of these isolates were still considered sensitive to this antimicrobial.…”
Section: Short Communicationmentioning
confidence: 88%
See 1 more Smart Citation
“…Unlike previous findings, resistance to penicillin was found in S. aureus and [15] CNS isolates (61.4% and 38.5%, respectively) [13], which was similar to our study (61.11% and 46.15%, respectively). The most effective antimicrobial substances for the treatment of streptococcal mastitis were β-lactams and macrolides [13,[21][22][23][24], as confirmed in our study. The rate of multiresistance to antibiotics was higher in Str.…”
Section: Discussionsupporting
confidence: 84%
“…Bacterial resistance to tetracycline was detected the most frequently [24][25][26][27]. Although β-Lactams are the best choice in the treatment of streptococcal mastitis [22][23][24][25][26][28][29][30], in our study, all isolates were fully susceptible to cefoperazone [29], penicillin, and ampicillin. The administration of clinoptilolite alone, and particularly in combination with selenium, increased the antibody titres against E. coli in the blood serum of heifers and calves [31].…”
Section: Discussionmentioning
confidence: 47%